Entry Inhibition and Modulation of Pro-Inflammatory Immune Response Against Influenza A Virus by a Recombinant Truncated Surfactant Protein D - Al-Ahdal, Mohammed N.; Murugaiah, Valarmathy; Varghese, Praveen M.; Abozaid, Suhair M.; Saba, Iram; Al-Qahtani, Ahmed Ali; Pathan, Ansar A.; Kouser, Lubna; Nal, Béatrice; Kishore, Uday (Frontiers in Immunology, 2018)
Surfactant protein D (SP-D), a C-type collagen containing lectin (collectin), is expressed in the mucosal secretion of the lung and contribute to the innate host defence against a variety of pathogens, including influenza A virus (IAV). SP-D has been shown to inhibit haemagglutination activity and infectivity of IAV, in addition to reducing neuraminidase (NA) activity. SP-D exhibits a strong anti-IAV activity by virtue of its carbohydrate recognition domain (CRD) binding to carbohydrate pattern (N-linked mannosylated) on NA and hemagglutinin (HA) of the IAV. Here, we demonstrate that a recombinant fragment of human SP-D (rfhSP-D), containing homotrimeric neck and CRD regions, acts as an entry inhibitor of IAV and down-regulates M1 expression considerably in infected pH1N1 as well as H3N2 IAV strains at 2h treatment. In addition, rfhSP-D down-regulated mRNA levels of TNF-α, IFN-, IFN-, IL-6 and RANTES production, as judged by qPCR, particularly during the initial stage of IAV infection of A549 cell line. rfhSP-D also interfered with IAV infection of Madin-Darby canine kidney (MDCK) cells through HA1 binding, as confirmed by luciferase reporter assay and far western blotting. Furthermore, rfhSP-D was found to reduce luciferase reporter activity of MDCK cells transduced with H1+N1 pseudotyped lentiviral particles in a dose-dependent manner, where 50% of reduction was observed with 10 μg /ml rhfSP-D. Thus, binding of rfhSP-D to HA1 and reduction in luciferase reporter activity is suggestive of a critical role of rfhSP-D in mediating the inhibition of IAV infectivity and that of pesudotyped lentivirus as an entry inhibitor. Multiplex cytokine array revealed that rfhSP-D treatment of IAV challenged A549 cells led to a dramatic suppression of some of the key pro-inflammatory cytokines and chemokines in the virus challenged A549 cells. In the case of pH1N1, soluble factors such as TNF-, INF-, IL-10, IL-12 (p40), VEGF, GM-CSF and eotaxin were considerably suppressed by rfhSP-D treatment at 24h. .